Evaluasi Kebijakan Pemerintah Pasca Bencana (Studi Kasus Bencana di Sulawesi Tengah) - Ahsan Samad; Erdiansyah Erdiansyah; Rina Wulandari (Universitas Muhammadiyah Gorontalo, 2020)
The purpose of this study is to identify and describe the impact and behavior of the community on post-disaster economic conditions in the city of Palu and to know the local government's public policies in handling these cases. Using qualitative methods with a case study approach, literature study, and secondary data processing from various social elements. In addition, data collection was carried out by interviewing informants who felt the direct impact of the earthquake, tsunami and liquefaction in Palu, Sigi and Donggala. The results showed that the post-disaster impact felt by the people of Palu City was generally in the